Chloral hydrate versus hydroxyzine HCL for sedation prior to pediatric sleep EEG recording. (1st October 2013) - Sezer, Taner; Alehan, Füsun
<x xml:space="preserve">Abstract</x> Objective: The sleep electroencephalogram (EEG) can reveal certain epileptiform activity patterns and facilitate localization of the focus. Sedation is often required for sleep EEG recording in pediatric patients, but there is no consensus on the optimal sedative. Hydroxyzine HCL (HH) and chloral hydrate (CH) are popular sedatives, but HH is rarely used for pediatric sleep EEG recording. The goal of this prospective study was to compare CH to HH for sleep induction efficacy, safety and effects on pediatric sleep EEG pattern. Research design and methods: A total of 282 children (age 4−9 years) referred to our sleep EEG laboratory and requiring sedation were randomly assigned to two groups: the CH Group (n = 141) received 50 mg/kg CH and the HH group (n = 141) received 1 mg/kg HH. If sedation was unsatisfactory, a second equal dose of the same sedative was administered 30 min later. Results: Sleep induction was less successful in the HH group compared to the CH group (p < 0.001). Sleep onset latency was significantly longer in the HH group (p < 0.01) and the proportion of HH group patients requiring a second sedative dose significantly higher (p < 0.01). There was no significant difference in the proportion of patients exhibiting epileptiform activity on the EEG or in adverse event rate between groups. Conclusion: CH was a superior sedative compared to HH owing to more rapid and successful sleep induction with no increase in adverse events.